Kinematic analysis of the snatch technique of Colombian 62 kg division weightlifters participating in the 52nd national championship, "Cartagena 2014" - Alfredo, R. M.; Ricardo, G.; Catalina, C.; Ricardo, C. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to identify the behaviour of some kinematic lineal variables during the execution of the snatch of the Colombian 62 kg division weightlifters participating in the 52nd National Championship in Cartagena in 2014, to recognize the movement patterns in this population, to identify the principal values of velocity peaks, the percentage of the height reached by the bar at its maximal point in relation to the weightlifter`s height, the relationship between the time of execution and the maximal peak of 3D velocity. All of the lifts, 100%, were analyzed of which 56% (n32) were valid.